La sarabande des apparences : les personnages d’Italiens dans l’œuvre de Jean-Philippe Toussaint - Christophe Meurée (MediAzioni)
Among the host of colourful characters who populate Jean-Philippe Toussaint’s works, both in literature and film, the Italian characters are undoubtedly the ones who come back most insistently, as are the journeys to Italy. Playing with stereotypes (eloquence, elegance and the art of painting) with subtlety, the writer seeks to give substance to a form of ideal to which he aspires.